1999
DOI: 10.1016/s0969-2126(00)88344-6
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the actin-binding region of utrophin reveals a head-to-tail dimer

Abstract: The crystal structure of the actin-binding region of utrophin suggests that these actin-binding domains may be more flexible than was previously thought and that this flexibility may allow domain reorganisation and play a role in the actin-binding mechanism. Thus utrophin could possibly bind to actin in an extended conformation so that the sites previously identified as being important for actin binding may be directly involved in this interaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
111
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(125 citation statements)
references
References 51 publications
14
111
0
Order By: Relevance
“…As estimated by the frictional coefficient, utrophin fragments assumed an elongated shape in the solution and became increasingly elongated as more spectrin-like repeats were added (Table I). This observation is consistent with the available molecular dimensions (16,28) and electron microscopy images of utrophin (12).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…As estimated by the frictional coefficient, utrophin fragments assumed an elongated shape in the solution and became increasingly elongated as more spectrin-like repeats were added (Table I). This observation is consistent with the available molecular dimensions (16,28) and electron microscopy images of utrophin (12).…”
Section: Resultssupporting
confidence: 91%
“…Utr261 cosedimented with F-actin in a saturable manner but with low affinity and localized to stress fibers when microinjected into fibroblasts (13,14). The crystallographic study of Utr261 revealed that its two CH domains are separated by an extended ␣-helix, suggesting that this actin binding region of utrophin may be more flexible than was concluded previously from the crystal structure of the analogous domain of fimbrin (15,16). Electron microscopy and image reconstruction analysis of Utr261 complexed with actin filaments established that the flexibility of CH domains within the utrophin amino terminus results in two different modes or stoichiometries of utrophin-actin interaction (17).…”
mentioning
confidence: 83%
“…Based on crystal structures showing a variable linkage between CH domains, it has been proposed that tandem CH domains are highly dynamic in both structure and function (13,17,18). Our study provides high-resolution structural information on one of these tandem CH domains in solution, showing that it is in equilibrium between two distinct conformations.…”
Section: Discussionmentioning
confidence: 70%
“…This type of ABD is not restricted to this family; more distantly related versions are found in other types of actin-binding proteins, such as filamin (Korenbaum and Rivero, 2002), but the lack of spectrin repeats excludes these other proteins from the spectrin superfamily. The structure of the ABD in dystrophin and utrophin has been solved, revealing a bundle of α-helices arranged in an extended head-to-tail dimer (Keep et al, 1999;Norwood et al, 2000).…”
Section: Spectrin Superfamily Motifsmentioning
confidence: 99%